CLICHE: Education Games for Climate Change Countermeasures - Fajar As'ari; Viena Patrisiane (SISFORMA, 2017)
Game as media education to introduced, delivering and teaching about knowledge by presenting the information that contains education materials through digital game. Many education field has been adapted into game as media educations, like history, arithmetic, etc. Social and environmental issues also can be adapted into a game to overcome the issues.Climate change, an issues that being world concern. Not only the impacts that being concern, the causes of climate change as important as the impacts. Minimizing behavior that can worsen climate change it also means minimizing climate change effect. One of education games has been created to educate people about climate change, inform about climate change itself and the way to minimizing the effects.In this paper will discuss about education games: CLICHE. Game which explain concisely the cause and some action to minimizing climate change cause through digital game play that will has impact to lessening the climate change effects.